Essais critiques - Barthes, Roland 1915-1980 (Paris Éditions du Seuil, 1964)
These critical essays are an essential part of Roland Barthes' reflection on theater and literature. Classical authors, such as Voltaire or Baudelaire, meet modern ones, such as Queneau or Robbe-Grillet.
Keywords: Literature; Crescendo; Theater; Philosophy